The use of phytochemicals as fumigants for the control of stored product insect pests - Eli Shaaya; Moshe Kostyukovsky (Journal of Entomological and Acarological Research, 2011)
The current study is aimed to evaluate the potential use of the known isothyiocyanates, as compared to a new isothyiocyanate (ITC) isolated from Eruca sativa (salad rocket) as fumigants for the control of stored product insects. The biological activity of methyl iodide (CH3I), carbon disulphide (CS2), benzaldehyde (C7H6O) and essential oils were also evaluated. The toxicity of the various fumigants was assessed against adults and larvae of a number of major stored product insects. ITCs are known to have high toxicity and only very low concentrations are needed for the control of stored product insects. Eruca sativa is used worldwide as a food supplement. Methylthio butyl ITC, the main bioactive component in this plant has high toxicity against insects, but lower mammalian toxicity as compared to other active ITCs. This makes this compound a potential candidate for insect control. Comparative studies with CH3I, CS2 and C7H6O showed that the first was the most active compound against stored product insects followed by the second and third. C7H6O was found active, but very sorptive; therefore it was less effective against insects. The activity of a large number of essential oils (EOs) isolated from aromatic plants was also evaluated.